The effect of vagotomy on bacterial translocation (A experimental study) - Mutlu DOĞANAY; N. Aydın KAMA; Erdal GÖÇMEN; Alparslan YAZGAN; Murat AKSOY; Alper TEKELİ; Gülüşan ERGÜL (Turkish Journal of Gastroenterology, 2019)
-